(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article analyzes the expression of illocutionary acts in English and Uzbek legal texts, with a focus on their communicative-pragmatic functions. Drawing on J. L. Austin’s and J. Searle’s speech act theory, the study highlights the prevalence of directive and declarative acts in both legal systems, which serve to impose obligations, establish prohibitions, or grant rights. The research demonstrates that in Uzbek legal discourse, illocutionary force is mainly realized through passive verb forms and modal words such as “majburdir,” “taqiqlanadi,” and “mumkin,” whereas in English legal discourse, modal auxiliaries like “shall,” “must,” and “may” are dominant. Comparative analysis reveals both universal features (e.g., obligation and prohibition as central categories) and language-specific features shaped by grammatical and stylistic norms of each language. The findings contribute to a better understanding of how legal norms are linguistically and pragmatically structured across different legal traditions.